Population dynamics, relative growth and sex change of the protandric simultaneous hermaphrodite Exhippolysmata oplophoroides (Caridea: Lysmatidae) close to an upwelling area - Pescinelli, Régis A. [UNESP]; Davanso, Thiago M. [UNESP]; Pantaleão, João A. F. [UNESP]; Carvalho-Batista, Abner [UNESP]; Bauer, Raymond T.; Costa, Rogério C. [UNESP] (Cambridge University Press (CUP), 2018)
The present study investigated the population dynamics of Exhippolysmata oplophoroides in an area influenced by upwelling, focusing on reproductive period, sex ratio, growth rate, longevity, mortality, relative growth and size of sex change. We also tested the hypothesis that the appendices internae increased in size with sex change from the male to the simultaneous hermaphrodite phase as possible replacements for the male appendices masculinae, which are reduced or lost at sex change. Population structure was assessed by the distribution of size frequency in three demographic groups: male phase, hermaphrodite phase with, and without embryos. For relative growth analysis, the length of the following structures was measured: carapace, second pleuron, first pereopod, second pereopod, appendices internae of the second to fifth pleopods, and appendix masculina. Smaller size classes were composed only by male-phase individuals. The sex ratio was significantly biased towards the simultaneous hermaphrodite phase. Reproduction was continuous in the population throughout the year. Slower growth rates but higher maximum body sizes than those estimated at other locations in south-eastern Brazil were observed in the population studied. Cooler temperatures and higher nutrient levels associated with upwelling may have produced this pattern of reproduction and growth, similar to that found in more southerly austral latitudes. We also found that sex change influences the relative growth of body structures such as the second pereopods, appendices internae, and appendix masculina, and hypotheses on the adaptive value of such allometric growth are proposed.
Keywords: allometry; growth; reproduction; sex allocation; sex ratio; upwelling